Investigating and Prioritizing Factors Affecting Technology Selection Using Multi Criteria Decision Making Methods in the National Iranian Petrochemical Company - Seyed Hossein Nouri; Tahmoures Sohrabi (Tehnički Glasnik, 2021)
Technology can be considered as the most important factor in changing human experiences. Much of the success of most top companies in the field of competition rests on innovative activities that often rely on technology. On the other hand, defining valid and reliable as well as measurable indicators is necessary in order to make the most accurate decision. This refers to the famous saying that anything that can be measured can be managed. Therefore, using various scientific sources, the present study seeks to identify indicators of appropriate technology selection and then, prioritize them using multi-criteria decision making methods in the National Iranian Petrochemical Company. For this purpose, first important factors have been identified by studying the research literature and utilizing experts’ opinion gathered and aggregated by Delphi method. Then, by these factors have been ranked by screening and final identification through a hybrid approach of TOPSIS and Shannon entropy. According to the obtained results, technology efficiency has the highest priority among the factors which shows that in technology with the highest level of efficiency must be transferred and used in petrochemical industry. The competitive effects of technology have the lowest priority which shows that it is the least impact for technology transfer in this industry, and it need less attention from the industry practitioners.